2005
DOI: 10.1289/ehp.7998
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Contamination of Commercial Maize Products during an Outbreak of Acute Aflatoxicosis in Eastern and Central Kenya

Abstract: In April 2004, one of the largest aflatoxicosis outbreaks occurred in rural Kenya, resulting in 317 cases and 125 deaths. Aflatoxin-contaminated homegrown maize was the source of the outbreak, but the extent of regional contamination and status of maize in commercial markets (market maize) were unknown. We conducted a cross-sectional survey to assess the extent of market maize contamination and evaluate the relationship between market maize aflatoxin and the aflatoxicosis outbreak. We surveyed 65 markets and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
458
6
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(503 citation statements)
references
References 7 publications
8
458
6
13
Order By: Relevance
“…Further, it is a potent immunotoxic agent in animals and also changes T-cell phenotypes in humans, which may aggravate the burden of infectious diseases in the developing world (Williams et al 2004;Jiang et al 2005;Wild 2007). AF contamination is an important problem in relation to food quality/food safety in Africa as a result of poor production and storage practices for major staples of the African diet (Hell et al 2000;Williams et al 2004Williams et al , 2010Lewis et al 2005). Studies in Uganda indicate that AF exposure is broadly similar to that reported from other African countries (Kaaya & Warren 2005).…”
Section: Please Scroll Down For Arti Clementioning
confidence: 95%
See 1 more Smart Citation
“…Further, it is a potent immunotoxic agent in animals and also changes T-cell phenotypes in humans, which may aggravate the burden of infectious diseases in the developing world (Williams et al 2004;Jiang et al 2005;Wild 2007). AF contamination is an important problem in relation to food quality/food safety in Africa as a result of poor production and storage practices for major staples of the African diet (Hell et al 2000;Williams et al 2004Williams et al , 2010Lewis et al 2005). Studies in Uganda indicate that AF exposure is broadly similar to that reported from other African countries (Kaaya & Warren 2005).…”
Section: Please Scroll Down For Arti Clementioning
confidence: 95%
“…Aflatoxin B 1 (AFB 1 ) is a potent hepatotoxic and genotoxic agent (Essigmann et al 1977;Wang & Groopman 1999), and has been evaluated as a Group I human carcinogen (sufficient evidence of carcinogenicity to humans) by the IARC, WHO (IARC 1993(IARC , 2002. Exposure to high levels of AFB 1 via the diet causes acute hepatotoxicity (aflatoxicosis) and death in humans, as demonstrated by recent outbreaks in Kenya, which were responsible for the deaths of more than 150 people (Azziz-Baumgartner et al 2005;Lewis et al 2005). Chronic exposure to low levels of AFB 1 is a risk factor in the aetiology of human hepatocellular carcinoma (HCC) in several regions of Africa and Southeast Asia, particularly in conjunction with hepatitis B virus infection (IARC 1993(IARC , 2002Wild & Hall 2000;Wogan et al 2012).…”
Section: Please Scroll Down For Arti Clementioning
confidence: 99%
“…Lewis et al. (2005) indicated that the contaminated homegrown maize may represent a source of aflatoxin contamination in market maize, especially when local farmers sold a portion of their farm household stores to market vendors. In Tanzania, Kamala et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to outbreak response activities, HSB scientists pursue research questions arising from these events. For example, research activities on the mitigation of aflatoxin-associated illness in Africa have been ongoing [1]. These activities are the result of a 2005 investigation into the largest aflatoxin-associated outbreak ever reported in Africa [1].…”
Section: Health Studies Branch Ncehmentioning
confidence: 99%
“…For example, research activities on the mitigation of aflatoxin-associated illness in Africa have been ongoing [1]. These activities are the result of a 2005 investigation into the largest aflatoxin-associated outbreak ever reported in Africa [1]. Another example is primary research into mercury levels in those who frequently consume fish caught in areas with elevated environmental burdens of mercury [2].…”
Section: Health Studies Branch Ncehmentioning
confidence: 99%